Суб'єкти запобігання злочинам проти виборчих прав громадян - Мозоль, С.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Проанализирована юридическая деятельность субъектов, осуществляющих предупреждение преступлений против избирательных прав граждан. Проведена классификация субъектов, предупреждающих преступления против избирательные прав граждан, и определены основные задачи противодействия такого рода преступлениям. In the article have been analyzed legal activities of the persons, charged with powers on prevention of crimes against voting rights of the public. Here's been defined classification of the persons charged with powers on prevention of crimes against voting rights of the public & stipulated the key assignments for counteraction to such a kind of crimes.